Serum potassium levels, cardiac arrhythmias, and mortality following non-ST-elevation myocardial infarction or unstable angina: insights from MERLIN-TIMI 36. Issue 1 (1st February 2017) - Patel, Ravi B; Tannenbaum, Sara; Viana-Tejedor, Ana; Guo, Jianping; Im, KyungAh; Morrow, David A; Scirica, Benjamin M
Abstract: Background: In acute coronary syndrome (ACS), potassium levels <3.5 mEq/L are associated with ventricular arrhythmias. Current guidelines therefore recommend a potassium target >4.0 mEq/L in ACS. Our study evaluated the association between potassium levels, cardiac arrhythmias, and cardiovascular death in patients with non-ST-segment elevation myocardial infarction or unstable angina. Methods: Potassium levels were measured in 6515 patients prior to randomization to receive either ranolazine or a placebo in the MERLIN-TIMI 36 trial. A seven-day continuous electrocardiographic assessment was obtained to determine the incidence of non-sustained ventricular tachycardia (NSVT) and ventricular pauses. The association between potassium levels and cardiovascular death was evaluated using a Cox proportional hazards regression model with multivariable adjustment. Results: NSVT lasting for at least eight consecutive beats occurred more frequently at potassium levels <3.5 mEq/L than at potassium levels ⩾5 mEq/L (10.1 vs. 4.5%, p =0.03 for trend), whereas the inverse pattern was observed for ventricular pauses >3 s, which occurred more frequently at potassium levels ⩾5 mEq/L than at potassium levels <3.5 mEq/L (5.9 vs. 2.0%, p =0.03 for trend). There was a U-shaped relationship between the potassium level at admission and both early and late risk of cardiovascular death. Compared with patients with potassium levels of 3.5 to <4 mEq/L, a potassium level <3.5 mEq/L was associated with an increased risk of cardiovascular death at day 14 (2.4 vs. 0.8%, HRadj 3.1, p =0.02) and at one year (6.4 vs. 3.0%, HRadj 2.2, p =0.01). The risk of cardiovascular death at one year was also significantly increased at potassium levels ⩾4.5 mEq/L and a similar trend was noted at potassium levels ⩾5 mEq/L. Conclusions: The lowest risk of cardiovascular death was observed in patients with admission potassium levels between 3.5 and 4.5 mEq/L. Both lower and higher levels of potassium were associated with tachyarrhythmias and bradyarrhythmias, suggesting a potential mechanistic explanation for the increased risk of cardiovascular death at the extremes of potassium homeostasis.